The scientific encyclopedic media: Its influence on learning outcomes and critical thinking skills - Andri Valen; Tio Gusti Satria (Jurnal Prima Edukasia, 2026)
A scientific encyclopedia is a learning medium that contains factual information, interesting illustrations, simple case studies, and reflective questions that guide students to explore, analyze, and communicate their findings using scientific methods. This study aims to measure the effect of media on learning outcomes and critical thinking skills of fifth-grade elementary school students in science. This study used a quantitative approach with associative and descriptive quantitative strategies. The sample consisted of students in class VA (experimental) and VB (control) at SDN 22 Kota Lubuklinggau. Scientific encyclopedia media was applied to the experimental class, and image media was applied to the control class. In data collection, the techniques used were written tests in the form of multiple-choice questions to measure learning outcomes and essay questions to measure critical thinking skills (pre-test and post-test). Data analysis and processing were carried out by determining question scores, descriptive analysis, prerequisite test analysis, and inferential analysis. The research design used was a pure experimental design with two groups. The results of this study indicate that scientific encyclopedia media significantly influence learning outcomes and critical thinking skills in social studies (learning outcomes and critical thinking skills in the experimental class were greater than those in the control class). These findings contribute to the existing literature on scientific encyclopedia media and their impact on student learning outcomes and critical thinking skills in social studies.